PdAuAg Alloy Nanoparticles on Nickel Foam as Anode for Passive Air-Breathing Formate Fuel Cell. Issue 6 (28th June 2021) - Pan, Bowei; Chen, Fuyi; Wang, Junpeng; Tang, Quan; Guo, Longfei; Jin, Tao; Peng, Chenxi; An, Liang; Chen, Yu
Abstract : A passive air-breathing formate fuel cell with PdAuAg alloy nanoparticles supported on the carbon nanotube (CNT) pasted on nickel foam (NF) as anode is reported in this work. With optimization, a maximum power density of 16 mW cm −2 with PdAuAg/CNT on NF as anode is achieved, which is 2.2 time of that achieved by using commercial Pd/C on NF (7.3 mW cm −2 ). Furthermore, the cell with PdAuAg/CNT on NF as anode can steadily discharge at 5 mA cm −2 for more than 28 h continuously. This is, to our knowledge, the best performance of passive air-breathing formate fuel cells reported so far and PdAuAg/CNT on NF as anode can be considered as the state-of-the-art for the passive air-breathing formate fuel cell. These results suggested that the PdAuAg/CNT catalyst probably provides an alternative avenue for developing the anode electrocatalysts for passive air-breathing formate fuel cell applications.